The Unblazed Trail: Bioinformatics and the Protection of Genetic Knowledge - Lawrence M. Sung (Washington University Journal of Law & Policy, 2002)
This Essay begins with a review of the legal treatment of biotechnology patents involving genetic information and addresses contemporary issues facing the federal courts and the USPTO. A consideration follows regarding the likely patent protection scenarios surrounding bioinformatics and proteomics. The Essay concludes with various proposals for the enhancement of progress in bioinformatics and proteomics, and other beneficiary research fields of genomics, through the securing of intellectual property rights.
Keywords: Patents; Biotechnology; Computational biology; Genetic research; United States